SKRINING ASAM URAT PADA ORANG DEWASA DI KELURAHAN TOMANG - Limanan, David; Rumawas, Marcella E; Santoso, Alexander Halim; Edbert, Bruce; Shafira Putri, Nawaika; Darma, Timothy Halomoan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
One of the non-communicable diseases that is of concern to the public is gout. Gout is a disease caused by the accumulation of urate crystals in tissues, especially joint areas due to chronic hyperuricemia. Without proper treatment, hyperuricemia can develop into chronic gout, the formation of tophus, severe kidney function disorders, and result in decreased quality of life. The aim of this activity is to check uric acid levels in the adult group, so that early intervention and prevention of hyperuricemia can occur and prevent gout. The activity began with a coordination meeting with community service partners, and it was agreed that PKM activities carried out on October 14, 2023, at 08.00-14.00 WIB. PKM activities begin with registration, then filling in personal data, then checking uric acid levels, and finally consulting with a team of doctors. The PKM activity was attended by 90 participants, consisting of 20 female participants (22%) and 70 male participants (78%) with the largest group aged 20 to 29 years, namely 28 participants (31%). The number of respondents who had experienced gout disorders was 7 participants (8%), while those who had no history of gout disorders were 83 participants (92%). The results of checking uric acid levels showed that 2 participants had low uric acid levels (2%), 76 participants (85%) had normal uric acid levels, and 12 participants (13%) had high uric acid levels. There are still quite a lot of participants who experience high uric acid levels, so education and routine uric acid checks are needed.